Assessment of Service Delivery Practice and Customer Satisfaction of Micro Finance Institutions: (The Case of ACSI, Gondar) (Global Journal of Management and Business Research, 2018)
The main aim of this study is to assess the service delivery practice in terms of quality and customer satisfaction in Amhara Credit and Saving Institution (ACSI) in case of Gondar city branches. The required data was collected from a sample of 314 customers. Simple random sampling technique was used to select the respondents. Both descriptive and inferential statistics were used to analyze and interpret the collected data. Questionnaires and report analysis were used as a data collection instruments. According to this research finding, the majority of customers are dissatisfied with the service delivery process of ACSI. Thus, credit and saving institutions are concerned about customer satisfaction and have to pay attention to understand their customers' preferences to survive in a competitive environment.
Keywords: Service Delivery Practice; Customer satisfaction; Micro-finance